Intrinsic and extrinsic factors in the conservation of ants and their use as bioindicators. - Bution, M.L.; Tango, M.F. de A.; Caetano, Flávio Henrique [UNESP] (My University, 2010)
Ant communities are sensitive to fragmentation responding through: extinction of specialist species compared with large habitats, invasion of generalist species, changes in community composition and richness of species. Because of these characteristics, this review aims at examining the main risks that ants have been facing to maintain their communities, as well as to report current conservation practices in Brazil and in the world.